D-dimer and international normalized ratio (INR) are correlated with tumor markers and disease stage in colorectal cancer patients - Kilic, Leyla; Yildiz, Ibrahim; Sen, Fatma Karagoz; Erdem, Mustafa Genco; Serilmez, Murat; Keskin, Serkan; Tas, Faruk (Ios Press, 2015)
BACKGROUND: The aim of this study is to evaluate the correlation of coagulation tests with various clinicopathological variables and tumor markers among colorectal cancer (CRC) patients. MATERIALS AND METHODS: Ninety-four CRC patients were included for evaluation of clinicopathological factors, coagulation assays and tumor marker levels. RESULTS: Metastatic disease was related with elevated INR (p = 0.03). Stage III patients had higher D-dimer values compared with stage II patients (p = 0.03). Correlation of tumor markers indicated a tendency towards elevated D-dimer levels for CEA values higher than median (p = 0.01). High CA 19-9 levels were also associated with higher INR (p = 0.007). Elderly age, distant metastasis, high CEA, CA-19-9 and LDH levels were associated with poorer overall-survival. CEA level was the only independent prognostic factor in multivariate analysis. CONCLUSIONS: Coagulation assays can be utilized as predictors of disease extent in CRC. Elevated D-dimer and INR values may indicate higher disease stage. Correlation of D-dimer levels with CEA supports their value for assessing tumor burden.
Keywords: Tumor marker; coagulation; colon cancer; D-dimer; CEA; CA 19-9